Design of an IoT-Based Nursing Assistant Robot Using Nodemcu Esp8266 and Blynk - Tongkad, Jainaldi; Ridwan, Wrastawa; Nasibu, Iskandar Zulkarnain; Abdussamad, Syahrir; Tansa, Salmawaty (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Work as a nurse requires direct contact with patients, for example when carrying drugs or changing IVs. However, since the COVID-19 pandemic, awareness to reduce direct contact with patients is increasingly needed. Moreover, direct contact with patients with infectious diseases, such as covid-19. For this reason, it is necessary to create a tool / robot that can connect nurses and patients, especially patients with infectious diseases. In this study, a robot design and implementation was made that can assist nurses in delivering drugs to patients, without having to make direct contact with patients. IoT-based designed robots using NodeMCU, ESP8266 and Blynk. NodeMCU ESP8266 is used as a data processor and smartphones are used as remote controls via the internet. Data from the smartphone is processed by NodeMCU then sends a signal to the robot actuator via the L298N driver motor to drive the wheels. Furthermore, the internet-connected IP camera is used for live streaming on smartphones through the V380 Pro application as a directional guide. Then to prevent collisions, the ultrasonic sensor HCSR04 will send data to NodeMCU ESP8266 if there is an obstacle at a distance of 30 cm in front of the robot, so that the robot will move backwards. The experimental results show that the robot can run well where the robot is controlled by a nurse using the Blynk IoT application and V380 Pro on a smartphone via internet media. Then the test was carried out with two methods, namely smartphones using the robot's local Wi-Fi connection and smartphones using cellular networks. The results showed that the response time of the application command on the smartphone to the robot or viewing video results from the IP Camera was affected by the condition of the internet network used.